(untitled) (Research, Society and Development, 2023)
The article, which is the result of a research conducted in 2020, with a school of early childhood education, located in the city of Parnaíba (PI), aims to present an analysis about the senses and meanings of the pedagogical practices, developed by educators, who work with music and dance in the school of early childhood education. The qualitative study used a methodological approach of the ethnographic type. The work is situated in the context of investigations about early childhood education, with emphasis on a theme that is linked to the thematic axis of culture, language and social interaction. The conclusions of the analysis point to the existence of conceptions and practices that focus on music and dance only as an instrument of relaxation, a form of entertainment, "ice-breaker" and artifice and not as central and strategic devices in the integral development of the child.